Assessing Students’ Perception of Internet of Things using Technology Acceptance Model - Vera Victor-Aigbodion (Didaktika: Jurnal Kependidikan, 2024)
This quantitative exploratory survey study examined accounting students’ acceptance of Internet of Things (IoT) technology among a sample of 343 accounting students from Nigerian public universities. The students’ mean age was 26.00±6.48years. Electronic copy of the research instrument was emailed to the students for completion. Statistical analysis of the research data was carried out at 0.05 level of significance. Results revealed significant positive associations of accounting students’ perceived usefulness with perceived ease of use and intention to use IoT technology. Also, results indicate that accounting students’ perceived ease of use correlated significantly with their intention to use IoT technology. The study also showed that there were no significant differences among the accounting students on the acceptance of IoT technology by gender and program type. The interaction of gender and program type did not produce any significant difference in students’ acceptance of IoT technology with regard to perceived usefulness; perceived ease of use; and intention to use. It is suggested that accounting students should be motivated to embrace the opportunities that abound in IoT technology. Finally, the researcher notes that IoT needs to be further addressed in the accounting education, even in advance to its potential mandate for financial reporting. Keywords:, , ;